Fiber laser welding of Ti–6Al–4V to Inconel 718 bimetallic structure via Cu/Ta multi-interlayer. (October 2021) - Hu, Yunfeng; Wu, Libin; Zhou, Peishan; Ye, Yangcheng; Wang, Bin
Abstract: In current work, we have used fiber laser welding (FLW) technology to manufacturing the Ti–6Al–4V (TC4) and Inconel 718 (IN718) bimetallic structure and to prevent the formation of brittle phases via Cu/Ta multi-interlayer. The results of this study showed that Cu/Ta multi-interlayer was very effective in preventing the formation of continuous brittle intermetallic layers of Ti–Ni and Ti–Cu. The good metallurgical bonds were presented at these interfaces between TC4 and IN718. As a result, the joints with gradational structure, i.e. TC4| (α+β Ti, Ta)ss | (β Ti, Ta)ss | Ta(s, s)+ (Cu(s, s)+ Ta(s, s)+ Ti3 Ni4 )| Cu(s, s)+ (Cu(s, s)+ Ta(s, s))| Ni(Ta, Fe, Cr)ss | IN718 can be formed, which can contribute high tensile strength of joints with the value of 396 MPa. Highlights: In this paper, we use a new Cu/Ta multi-interlayer layer for fiber laser welding TC4 and IN 718. The formation of continuous brittle intermetallic layers of Ti–Ni and Ti–Cu is effectively prevented. The tensile strength of the bimetallic structure with the Cu/Ta multi-interlayer was 396 MPa, which reached that of the 42.6% and 45.8% of the tensile strength of TC4and IN718, respectively. In the present work, defect-free, dissimilar FLW of the bimetallic structure was successfully achieved by using Cu/Ta multi-interlayer. The typical microstructure of joint is TC4| (α+β Ti, Ta)ss| (β Ti, Ta)ss| Ta(s, s)+ (Cu(s, s)+ Ta(s, s)+ Ti3Ni4)| Cu(s, s)+ (Cu(s, s)+ Ta(s, s))| Ni(Ta, Fe, Cr)ss| IN718.